2021
DOI: 10.3389/fendo.2021.630550
|View full text |Cite
|
Sign up to set email alerts
|

Low Prognosis by the POSEIDON Criteria in Women Undergoing Assisted Reproductive Technology: A Multicenter and Multinational Prevalence Study of Over 13,000 Patients

Abstract: ObjectiveTo estimate the prevalence of low-prognosis patients according to the POSEIDON criteria using real-world data.DesignMulticenter population-based cohort study.SettingsFertility clinics in Brazil, Turkey, and Vietnam.PatientsInfertile women undergoing assisted reproductive technology using standard ovarian stimulation with exogenous gonadotropins.InterventionsNone.Main outcome measuresPer-period prevalence rates of POSEIDON patients (overall, stratified by POSEIDON groups and by study center) and the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…On the other hand, women aged 35 years and older with similar outcomes are categorized as POSEIDON Group 2a and 2b. Recent evidence confirmed that Poseidon groups 1 and 2 have significantly lower live birth rate (LBR) when compared with women having more than 9 oocytes retrieved, confirming the capability of Poseidon classification to identifying different low prognosis segments [ 7 ]. The exact etiology of uIOR or POSEIDON-1 remains unclear.…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, women aged 35 years and older with similar outcomes are categorized as POSEIDON Group 2a and 2b. Recent evidence confirmed that Poseidon groups 1 and 2 have significantly lower live birth rate (LBR) when compared with women having more than 9 oocytes retrieved, confirming the capability of Poseidon classification to identifying different low prognosis segments [ 7 ]. The exact etiology of uIOR or POSEIDON-1 remains unclear.…”
Section: Introductionmentioning
confidence: 96%
“…Women characterized by a reduced ovarian sensitivity (or "hypo-response") are characterized by reduced the number of eggs retrieved despite the normal ovarian reserve. Evidence indicates that hypo-response is typically observed in women with reduced IVF prognosis (5)(6)(7)(8)(9). So far, several ovarian sensitivity indicators have been proposed (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Women characterized by a reduced ovarian sensitivity (or “hypo-response”) are characterized by reduced the number of eggs retrieved despite the normal ovarian reserve markers. Evidence indicates that hypo-response is typically observed in women with reduced IVF prognosis [ 6 10 ]. So far, several ovarian sensitivity indicators have been proposed [ 11 ].…”
Section: Introductionmentioning
confidence: 99%